Impact of Virtuality and the Use of TIC by University Teachers in Times of the Covid 19 Pandemic - Soto Carrión, Carolina (2023)
The Covid19 pandemic has abruptly changed the way of teaching university teachers. Objective: to establish the impact of the change from face-to-face to virtuality in the teaching-learning process of university professors at the Technological University of the Andes, Abancay. Method: In the study, 151 teachers from the different careers and Faculties of the university participated, under a random shot. The intervening instrument has been a structured survey of 10 questions and a five-level scale and other closed ones sent by institutional emails, Results: The teachers of the Technological University of the Andes have not had any virtual means at the beginning of the pandemic and it was The change from face-to- face to virtuality had a great impact, with teachers who react quickly to the use of technologies (TIC) and some have been adapting with difficulty in subsequent months. Discussion: The university had difficulties at the beginning about the conditions and facilities for access to technological tools, connectivity, implementation, but there was a difficult but quick reaction from the teachers. Conclusions: University teachers after the start of the Covid19 pandemic, have adapted with many restrictions to the virtual modality, for having been a sudden, unexpected change Teachers have adopted virtual strategies with the use of Tic tools, accepting in a 41 % the Moodle system for the development of learning sessions at the University.